PP.LB03.06: THE EFFECT OF AIRCRAFT NOISE EXPOSURE ON BLOOD PRESSURE AND ASYMPTOMATIC ORGAN DAMAGE. (June 2015) - Rojek, M.; Rajzer, M.; Pizon, T.; Skalski, P.; Czarnecka, D.
Abstract : Objective: To investigate effects of exposure to aviation noise on blood pressure, prevalence of arterial hypertension and its asymptomatic organ damage i.e. arterial stiffness, left ventricular hypertrophy and diastolic dysfunction. Design and method: Study group (n = 101 pts) was randomly recruited among inhabitants of area exposed to high aircraft noise levels, exceeding 60db (A). Control group (n = 100 pts) was recruited accordingly in area of low aircraft noise exposure, below 55 db (A). Sites selection was based upon acoustic maps. Inclusion criteria involved age (40–65 yrs) and time of residence in given area (min. 3 yrs). Anthropometric and demographic data were collected via questionnaire. In both groups following examinations were performed: office blood pressure measurement (SBP, DBP) using Omron M5-I device; arterial stiffness measurements- carotid-femoral pulse wave velocity (PWV) and central blood pressure (cSBP, cDBP) using SphygmoCor® device; echocardiographic measurements of left ventricular diastolic function (E/A, E/e'), mass (LVM) followed by mass index determination (LVMI) using VIVID-7 GE device. Results: Both groups were of equal age (53.6 ± 8.9 vs 52.2 ± 10.2 yrs, p = 0.42), BMI (27.1 ± 4.4 vs 26.9 ± 5.3 kg/m2, p = 0.8) and sex ratio (49 % women vs 52 % women). SBP (145.7 ± 20.0 vs 137.6 ± 18.8 mmHg, p = 0.03) and DBP (89.0 ± 11.6 vs 78.6 ± 8.6, p = 0.000001) values were higher in study group. Same as prevalence of hypertension (40% vs 24%, p < 0.05). Indicators of asymptomatic organ damage altered significantly among groups: PWV (10.3 ± 2.0 vs 9.5 ± 1.7 m/s, p = 0.04), cSBP (133.4 ± 19.3 vs 123.3 ± 18.6 mmHg, p = 0.007), cDBP (88.6 ± 11.1 vs 78.7 ± 9.6 mmHg, p = 0.000004), LVMI (108 ± 28.2 vs 102 ± 23.00 g/m2, p = 0.004) were higher in study group, while E/A ratio was lower in study group (1.0 ± 0.33 vs 1.3 ± 0.46, p = 0.009). No difference was observed between groups in E/e' ratio (8.36 ± 2.7 vs 8.15 ± 2.74, p = 0.7). Conclusions: Long-term exposure to aircraft noise is associated with higher office blood pressure values, prevalence of arterial hypertension and incidence of its heart and arterial asymptomatic organ damage.